“Nada básico!” : moda e consumo de roupa no Camelódromo de Cuiabá - Silva, Inara Fonseca Ferreira Mandu da (2012)
By the trite and complex practice of the clothing’s consumption at the Shopping Popular we intend to investigate and analyze the phenomenon of the contemporary consumption and appropriation of fashion between the parties at the Cuiabá’s camelódromo (sellers and buyers), the most of them coming from a subaltern class. For this reason, will be realized conversations with the authors Néstor Canclini, Arjun Appadurai, Massimo Canevacci, Gilles Lipovetsky and Walter Mignolo.